PERAN KEPEDULIAN PADA LINGKUNGAN MEMEDIASI PENGETAHUAN TENTANG LINGKUNGAN TERHADAP NIAT PEMBELIAN PRODUK HIJAU - Tanaya, Decky; Rastini, Ni Made (E-Jurnal Manajemen, 2016)
Environmentally friendly product is a product made in anticipation of environmental damage sustained as a form of innovation. This study aims to determine the role of environmental care in mediating the knowledge of the environment against the intention of purchasing green products injection motor Yamaha Blue Core. The number of samples taken as many as 100 people in the city of Negara, the methods used non-probability sampling and analytical techniques that SEM analysis based PLS (Partial Least Square). Findings from this study indicate that knowledge of the environment has a positive and significant impact on purchase intentions motorcycle products Blue Core Brand Yamaha. Knowledge of the environment positive and significant impact on environmental care. Concern for the environment positive and significant impact on purchase intentions of green products, and concern for the environment does not mediate the effect of environmental knowledge of the intention of purchasing green products.
Keywords: green marketing, green products, environmental knowledge, concern for the environment, the intention of purchasing green products.